Elemental Assessments Of South China Sea Marine Sediments Along The East Coast Of Peninsular Malaysia - Ebrahim Saraee, Khadijeh Rezaee (2010)
Malaysia is located in the west of the South China Sea and is divided into two major land masses, i.e., Peninsular Malaysia and East Malaysia on the Island of Borneo, with a total coast line of 4675 km (Peninsular Malaysia 2068 km; East Malaysia 2607 km). As most seas, the majority of pollution occurs in the South China Sea arise from the land namely waste that comes from large cities (sewage, industrial waste and hydrocarbons) and agricultural runoff (nutrients, pesticides and fertilizers). The aim of this research is to access information on horizontal elemental distribution of coastal surface sediments and on vertical elemental distribution of offshore core sediments and to determine the status of pollution in the surface and core marine sediments. The results of this research together with experimental data from other researches on marine sediments on the east coast of Peninsular Malaysia may be used to establish a baseline data for this region. All together 43 elements were identified and then classified according to heavy metals (As, Cd, Cu, Cr, Ni, Pb and Zn), trace elements (B, Ba, Be, Bi, Br Co, Cs, Ga, Ge, Hf, Li, Mo, Nb, Sc, Rb, Sb, Sn, Sr, Ta, V, W, Y and Zr), rear earth elements (Ce, Dy, Eu, La, Lu, Nd, Sb, Sm and Yb), major elements (Al, Ca, K, Fe, Mg, Mn Na, P, S and Ti), and actinides elements (Th and U) depending on their physical and chemical characteristics. The elemental concentrations of the surface sediments from 10 stations and the core sediments from 5 stations have been determined using the Instrumental Nuetron Activation Analysis (INAA) at Nuclear Agency Malaysia and the Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES) at Geological Survey of Iran (GSI) laboratories. To know the status of contamination in heavy metals and trace elements, the enrichment factor, geoaccumulation index (Igeo) and modified degree of contamination (mCd) methods were used to interpret the results. Where appropriate the linear regression analysis, pearson‘s correlation factors, first and second of the principal component analysis and the cluster analysis were performed to determine the relationships between obtained results. For the surface elemental distributions, heavy metal Pb was found to be originated from anthropogenic sources at the stations at the larger river mouths of Kelantan, Pahang and Rompin rivers, possibly due to land-based anthropogenic activities, automotive emission and gas industries. However, the average Igeo and mCd values indicate that the heavy metals of the surface sediments are uncontaminated in all sampling stations. The same situation was true for trace elements, except for Hf which has the enrichment factor greater than 2 in EC8 station. The high concentration of Hf at this station was a natural occurring because of it has negative correlation with Zn in this station similarity with those in nature. Shale averages and chondorite normalized were used to normalize rare earth elements (REEs). Ce was found anthropogenic element, possibly due to occurrence of +4 oxidation states, while other REEs are of non-anthropogenic sources. Most REEs have lower concentrations at the larger river systems and Ce and Eu anomalies occurred in samples taken from the mouths of Kelantan and Pahang rivers. For major elements, Al, Ca, Mg, Na, and Ti were of anthropogenic sources, possibility due to tropical weathering. Both actinides Th and U were non-anthropogenic for all sampling stations except for Kuala Dungun possibility due to a radioactive related factory like among in that area. For the vertical element distribution, heavy metals As, Cd and Pb; trace elements Br, Hf, Sr and Zr; major elements Ca and Na and actinide element Th were of anthropogenic sources. However, by considering the average Igeo and mCd values, most of the layers in the east coast of Peninsular Malaysia were uncontaminated. Only Hf was the most polluted in affected stations and were classified as moderately to stronger contamination. The chondrite-normalized ratios of REEs showed LREEs enrichment and flat HREE depletion. No Ce anomaly was observed in sediments of all layers in all the stations. Overall, the results showed that the normalized patterns of REEs of the core sediments followed a general pattern of REEs of the world.